2005
DOI: 10.1111/j.1365-2575.2005.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a model of consumer use of mobile information and communication technology in LDCs: the case of sub‐Saharan Africa

Abstract: Using theories of technology acceptance and technology transfer, we identified factors affecting the use of mobile information and communication technology (mobile ICT) in the least developed countries (LDCs), specifically sub-Saharan Africa. From a literature review, we developed a research model to describe factors that impact mobile ICT use and formulated a series of hypotheses about them. We then surveyed mobile ICT users in Kenya and Nigeria and created a structural model to examine our hypothesized relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(108 citation statements)
references
References 64 publications
(127 reference statements)
7
101
0
Order By: Relevance
“…Although a growing body of literature has highlighted the advantages and valuable aspects of mobile services including m-banking (e.g., Anckar and D'Incau, 2002;Riivari, 2005), consumers' primary reasons for adopting and using mobile services remain unclear (Meso et al, 2005), especially with respect to continuous usage. Research has revealed several factors that contribute to the usage of text-based (SMS) m-banking in Finland such as convenience, access to the service regardless of time and place, privacy, and savings in time and effort (Suoranta and Mattila, 2004;Laukkanen, 2007).…”
Section: Reasons For Continuous Usage Of M-banking Servicesmentioning
confidence: 99%
“…Although a growing body of literature has highlighted the advantages and valuable aspects of mobile services including m-banking (e.g., Anckar and D'Incau, 2002;Riivari, 2005), consumers' primary reasons for adopting and using mobile services remain unclear (Meso et al, 2005), especially with respect to continuous usage. Research has revealed several factors that contribute to the usage of text-based (SMS) m-banking in Finland such as convenience, access to the service regardless of time and place, privacy, and savings in time and effort (Suoranta and Mattila, 2004;Laukkanen, 2007).…”
Section: Reasons For Continuous Usage Of M-banking Servicesmentioning
confidence: 99%
“…Users' initial level of 21 trust in the recommendation results increased when results were accompanied by justification 22 for outcomes [29]. 23 Accessibility also affected perceived ease of use for mobile data services [46] as most of the recommendation functionality is using collaborative recommendation 20 algorithm which uses preferences of a group of people who have similar age, occupations, 21 ethnic background and so on. On the other hand, UA is related with the purpose of MRSs as 22 people use MRSs to reduce alternatives therefore to reduce uncertainty in making purchase 23 decision.…”
Section: Level 22mentioning
confidence: 99%
“…Meso et al (2005) conclude that perceived ease of use is an important construct for technology usage. As a community perceives the services offered to be easy to utilize, they will be emboldened to use it persistently, which in turn facilitates sustainable usage of the services offered (Rogers, 2003).…”
Section: Effort Expectancy (Ee)mentioning
confidence: 99%